PERAN AUDIT INTERNAL UNTUK PELAKSANAAN PENCEGAHAN FRAUD DENGAN GOOD CORPORATE GOVERNANCE SEBAGAI VARIABLE INTERVENING PADA PT. BANK PEMBANGUNAN DAERAH MALUKU DAN MALUKU UTARA - Talla, Alend; Simanjuntak, Pranatalindo; Tjio, Sari Tamayani (Kupna Akuntansi: Kumpulan Artikel Akuntansi, 2024)
There have been many cases of fraud that show the weakness of internal control in management at PT Bank Maluku Malut. Thus it is hoped that the emergence of GCG can help banking management to minimize and reduce the number of frauds that occur at the bank. This research was made to see the implementation of internal audit at PT Bank Maluku Malut plays an important role in realizing Good Corporate Governance so that through the principles of GCG the company can efficiently reduce the number of frauds. The study used the Partial Least Square (PLS) approach as data analysis. PLS is a component or variant-based Structural Equation Modeling (SEM) equation model. The data used is primary data, which is collected through a research questionnaire, with a research population of 30 people, namely all auditors and internal control branches at PT Bank Maluku Malut. The results of this study indicate that the role of the Internal Auditor has a significant influence in realizing Good Corporate Governance while the Internal Audit Role does not have a significant influence on fraud prevention, but if using Good Corporate Governance (GCG) as an intervening variable, the role of internal audit will affect Fraud Prevention with a significance level of α = 0.05.